The practice in teacher education through the interactive digital whiteboard: an experience report (Revista Internacional de Formação de Professores, 2020)
This paper deals with a school intervention project built upon the idea of “the experience report as an educational research method”. The project was developed in a municipal public school, aimed at teachers and their training in the use of the digital whiteboard as a teaching tool. In the end, it was identified a clear need for an institutional effort for the interactive board (and any other technological apparatus) to be incorporated into school processes, including investments in infrastructure and maintenance, as well as encouraging its constant usage. Only in this way, continuous training efforts given off by teachers will have a forceful impact on the school daily life.
Keywords: Interactive digital whiteboard. Informatics in Education. Teacher Education.